The coexistence of sarcoidosis and hepatitis C: A case report - Ahmet ERDİL and Ahmet TÜZÜN and Abdurrahman KADAYIFÇI and Ahmet UYGUN and İsmail YÜKSEKOL and M. Salih DEVECİ and Kemal DAĞALP (Turkish Journal of Gastroenterology, 2019)
-